Trendy konsumenckie a wydajność mleczna i zawartość białka w mleku krów rasy Holsztyńsko-Fryzyjskiej = Consumer trends in relationto milk yield and protein content in milk of dairy Holstein-Friesian cows - Milena Górecka; Oliwia Duszyńska-Stolarska; Angelika Habel; Maria Bogdzińska (Kazimierz Wielki University, 2015)
Górecka Milena, Duszyńska-Stolarska Oliwia, Habel Angelika, Bogdzińska Maria. Trendy konsumenckie a wydajność mleczna i zawartość białka w mleku krów rasy Holsztyńsko-Fryzyjskiej = Consumer trends in relationto milk yield and protein content in milk of dairy Holstein-Friesian cows. Journal of Education, Health and Sport. 2015;5(6):251-257. ISSN 2391-8306. DOI 10.5281/zenodo.18559 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A251-257 https://pbn.nauka.gov.pl/works/565795 http://dx.doi.org/10.5281/zenodo.18559 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 10.06.2015.   Trendy konsumenckie a wydajność mleczna i zawartość białka w mleku krów rasy Holsztyńsko-Fryzyjskiej   Consumer trends in relationto milk yield and protein content in milk of dairy Holstein-Friesian cows   Milena Górecka, Oliwia Duszyńska-Stolarska, Angelika Habel, Maria Bogdzińska1 1University of Technology and Life Sciences in Bydgoszcz, Department of Genetics and General Animal Breeding   Streszczenie Bydło mleczne jest hodowane głównie z uwagi na duże ilości pozyskiwanego mleka, które jest bogate w białko. Produkowane mleko jest ważne w diecie dzieci, młodzieży i osób starszych. Posiada ono niezbędne składniki do budowy kości i regeneracji komórek. Wydajność mleczna, razem z zawartością białka w mleku są najważniejszym parametrem klasyfikującym jego przydatność. Jednym z gatunków bydła mlecznego jest rasa Holsztyńsko - Fryzyjska. Obejmuje ono bydło czarno - białe i czerwono - białe pochodzenia krajowego i zagranicznego oraz potomstwo pochodzące z kojarzenia pomiędzy odmianami barwnymi. Badanie obejmowało grupę o odmianie HO - czyli bydło tylko odmiany czarno - białej. Ta grupa obejmowała dwa stada: jedno  wolnowybiegowe, gdzie badaniami objęto 149 krów i drugie - alkierzowe o liczebności 150 sztuk. Średnia wydajność mleczna w pierwszej grupie to 8988 kg mleka w 305-dniowej laktacji, natomiast w drugiej grupie wynik ten kształtował się na poziomie 8421,74 kg mleka. Celem badania było wykazanie wpływu wybranych czynników na wydajność mleczną i zawartość białka w mleku. W tym doświadczeniu był to system utrzymania oraz kolejność laktacji.   Słowa kluczowe: wydajność mleczna, zawartość białka, bydło mleczne Summary Dairy cattle are breeding for the ability to produce large quantities of milk which is plentiful of protein. Produced milk is an important in the diet of children, youth and the elderly. It has necessary factors to build bones and regenerate cells. Milk yield, together with a protein content in milk is the most important parameter determining the profitability of farming. One of the species of dairy cattle are Holstein - Friesian cows. They are include black-and-white and red-and-white domestic and foreign origin and offspring from the mating between varieties of colored cattle. The research was conducted on herd HO variety of Holstein - Friesian breed - it means the only black-and-white cattle domestic and foreign origin and their offspring. This group consisted of two herds. One of it - 149 cows in a free range housing system and the second - 150 cows kept indoor. The average milk yield in first group is 8988 kg of milk per 305-day lactation and in the second group it's 8421,74 kg of milk. The aim of this study is to demonstrate the influence of selected factors on milk yield and protein content in milk of cows. In this research as selected factors were housing system and lactation sequence.   Key words: milk yield, protein content, dairy cows.